Moral sensitivity and caring behavior in nursing interns: the mediating role of empathy - Chen, Jin yan; Chen, Hong fang; Wang, Xing huan; Zong, Qing zhen; Yao, Zhen zhen (Frontiers in Public Health, 2024)
The main purpose of this study is to analyze the relationship among moral sensitivity, empathy, and caring behaviors, and to explore the mediating effect of nursing interns' empathy between moral sensitivity and caring behaviors.: A cross-sectional survey was conducted on 261 nursing interns from 2 Grade 3A Hospitals in Xi'an, from August to September 2022. The questionnaires used in the survey include the General Information Questionnaire (GIQ), Moral Sensitivity Questionnaire-Revised Version into Chinese (MSQ R-CV), the Chinese version of Jefferson Empathy Scale (JSE), and the Chinese version of the Caring Behavior Inventory (C-CBI).Data were analyzed through descriptive statistics, one-way ANOVA and Pearson's correlation coefficient, and the mediating effect of empathy was tested through structural equations. Results:The overall mean of moral sensitivity of nursing interns in 2 Grade 3A Hospitals in Xi'an is (40.84±8.73), the overall mean of empathy is (100.51±21.56), and the overall mean of caring behavior is (113.81±21.05).Moral sensitivity and caring behavior of nursing interns are positively correlated(r=0.376, P<0.01), empathy and moral sensitivity of nursing interns are positively correlated(r=0.336, P<0.01), and empathy and caring behavior of nursing interns are positively correlated(r=0.394, P<0.01).The empathy of nursing interns has a mediated effect on the relation between moral sensitivity and caring behavior. The mediated effect value was 0.14 accounting for 31.82% of the total effect. Conclusions:The moral sensitivity of nursing interns can have a direct impact on their caring behaviors and an indirect impact on their caring behaviors with empathy mediating.Therefore,nursing educators and hospital administrators should adopt targeted interventions to improve the moral sensitivity and empathy of nursing interns, and which is further beneficial to improve nursing interns' 2 caring behaviors and the quality of nursing care, to reduce nurse-patient conflicts, and to stabilize the nursing team.